2010
DOI: 10.1002/chem.201000364
|View full text |Cite
|
Sign up to set email alerts
|

Cubic Mesoporous Titanium Phosphonates with Multifunctionality

Abstract: Cubic mesoporous titanium phosphonate materials with bridged organic groups inside the framework were synthesized by means of a one-pot hydrothermal autoclaving process, with the assistance of cationic surfactant cetyltrimethylammonium bromide. 1-Hydroxyethylidene-1,1-diphosphonic acid was used as the coupling molecule. A typical cubic mesophase with surface area of 1052 m(2) g(-1) and pore size of 2.6 nm was confirmed by XRD, TEM, and N(2) sorption analysis. The organophosphonate groups were homogeneously inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
63
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 44 publications
4
63
0
2
Order By: Relevance
“…21) In the case of the bis-phosphonic acid 4, cubic mesoporous Ti-phosphonates were obtained using CTAB as a template, 45) while Zr-phosphonates with a hierarchically porous texture were synthesized in the presence of triblock copolymers (F127 or P123) using a mild solvent evaporation strategy. 46) Mesoporous Zr-phosphonates with a high P/Zr ratio (around 3) and high POH content were prepared using phosphonic acids 4, 6 or 9 (Scheme 2) in the presence of CTAB.…”
Section: )mentioning
confidence: 99%
“…21) In the case of the bis-phosphonic acid 4, cubic mesoporous Ti-phosphonates were obtained using CTAB as a template, 45) while Zr-phosphonates with a hierarchically porous texture were synthesized in the presence of triblock copolymers (F127 or P123) using a mild solvent evaporation strategy. 46) Mesoporous Zr-phosphonates with a high P/Zr ratio (around 3) and high POH content were prepared using phosphonic acids 4, 6 or 9 (Scheme 2) in the presence of CTAB.…”
Section: )mentioning
confidence: 99%
“…膦酸钛可以看做一种对二氧化钛的磷、碳共掺 杂改性, 从而显示较好的光催化效果. 例如, CMTP 材 料 [48] [51] . 具有磺酸基或膦 酸基团的酞菁染料可以作为耦合分子, 在表面活性剂 F127 诱导自组装下, 以 TiCl 4 为前驱体, 通过一步水热 反应合成出具有六方介孔的杂化材料 [51] .…”
Section: 催化unclassified
“…在阳离子表面活 性剂 CTAB 的存在下, 通过一步高压水热合成方法我们 首次合成出了立方介孔膦酸钛材料(Cubic mesoporous titanium phosphonate, CMTP) [48] , [48] Figure 3 The structural representation and TEM images of the synthesized CMTP material (a) and the synthesis condition map of periodic mesoporous titanium phosphonates mainly considering the addition amounts of reagents and surfactant (b) [48] [13,22,46,50~52] . 例 如, 在 CTAB 辅助下, 以 HEDP 作为膦源合成出了孔径 为 2.6 nm 的立方介孔膦酸钛材料 CMTP [48] . 以 C 16 EO 10 为表面活性剂, 结合高压水热法和挥发诱导自组装 (EISA)的方法可以合成出孔径 2.8 nm 的有序介孔膦酸 钛材料 [39] .…”
unclassified
“…Many amine-functionalized mesoporous organic-inorganic hybrid materials [69,70] were proven to be efficient in the adsorption of CO 2 through the formation of carbamate species between the solid aminebased adsorbent and the gaseous CO 2 under dry conditions. The CO 2 uptake of the cubic mesoporous titanium phosphonates was approximately 1.0 mmol g À1 at 35 8C, [50] which was much higher than for some pure silica adsorbents and comparable with some amino-modified mesoporous silica with similar surface areas. [71,72] This indicates that, because of the phosphonate groups of the organic-inorganic network, the Van der Waals forces between CO 2 and the hybrid materials are much stronger than between CO 2 and the pure inorganic adsorb- www.chemsuschem.org ents.…”
mentioning
confidence: 97%
“…Further experiments confirmed that, besides the ethylenediamine groups, many electronegative groups or atoms, such as ÀOH, ÀSH, and N, could contribute toward metal ion adsorption. Cubic mesoporous titanium phosphonates (surface area: 1052 m 2 g À1 ), synthesized by using HEDP as the coupling molecule, had an adsorption capacity for Cu 2+ ions (28.5 mmol g À1 ), [50] which was higher than that of irregular mesoporous titanium phosphonates (surface area: 377-511 m 2 g À1 ). [66] Mesoporous aluminum phosphonates, which were constructed from BHMTPMP, exhibited much larger adsorption capacities than those constructed from ATMP with a similar surface area and pore volume.…”
mentioning
confidence: 99%